An Altered Mycobacterium tuberculosis Metabolome Induced by katG Mutations Resulting in Isoniazid Resistance - Loots, Du Toit (American Society for Microbiology, 2014)
The most common form of drug resistance found in tuberculosis (TB)-positive clinical samples is monoresistance to isoniazid. Various genomics and proteomics studies to date have investigated this phenomenon; however, the exact mechanisms relating to how this occurs, as well as the implications of this on the TB-causing organisms function and structure, are only partly understood. Considering this, we followed a metabolomics research approach to identify potential new metabolic pathways and metabolite markers, which when interpreted in context would give a holistic explanation for many of the phenotypic characteristics associated with a katG mutation and the resulting isoniazid resistance in Mycobacterium tuberculosis. In order to achieve these objectives, gas chromatography-time of flight mass spectrometry (GCxGC-TOFMS)-generated metabolite profiles from two isoniazid-resistant strains were compared to a wild-type parent strain. Principal component analyses showed clear differentiation between the groups, and the metabolites best describing the separation between these groups were identified. It is clear from the data that due to a mutation in the katG gene encoding catalase, the isoniazid-resistant strains experience increased susceptibility to oxidative stress and have consequently adapted to this by upregulating the synthesis of a number of compounds involved in (i) increased uptake and use of alkanes and fatty acids as a source of carbon and energy and (ii) the synthesis of a number of compounds directly involved in reducing oxidative stress, including an ascorbic acid degradation pathway, which to date hasn't been proposed to exist in these organisms.